FIRM ATTRIBUTES AND CASH HOLDINGS OF LISTED PHARMACEUTICAL FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
The study investigated the effect of firm attributes on the cash holdings of listed pharmaceutical firms in Nigeria. The specific objective was to determine the effect of firm leverage, firm profitability and firm size on cash and cash equivalent of listed pharmaceutical firms in Nigeria. Ex-post Facto research design was deployed in the study. The study's population consists of seven firms listed in the pharmaceutical sector of the Nigerian Exchange Group. The study utilized a purposive sampling technique, including a sample of five (5) firms that published their annual reports from 2014 to 2023. Secondary data were obtained from the annual reports of the firms included in the sample for a ten-year period spanning 2014 to 2023. Descriptive analysis was used to summarise the dataset whereas Fixed Effect Regression (at the discrimination of Hausman Specification) was used in testing the hypotheses. The findings showed that: firm leverage has a significant positive effect on cash and cash equivalent of listed pharmaceutical firms in Nigeria (β = 0.168115; p-value = 0.0434); firm profitability has a significant positive effect on cash and cash equivalent of listed pharmaceutical firms in Nigeria (β = 0.258447; p-value = 0.0352); firm size has a significant positive effect on cash and cash equivalent of listed pharmaceutical firms in Nigeria (β = 0.356278; p-value = 0.0005). In conclusion, firms with higher leverage, greater profitability, and larger size tend to hold more cash, driven by the need to manage financial risks, invest in growth opportunities, and maintain operational flexibility. The study recommends that management of highly leveraged firms should prioritize maintaining adequate cash reserves to ensure they can meet debt obligations and reduce financial risk in order to help safeguard the firm against potential cash flow shortages and enhance financial stability
Keywords: Cash; Cash Equivalent; Cash Holdings; Firm Attributes; Firm Leverage; Firm Profitability; Firm Size